Neuroinflammation: An astrocyte perspective - Lee, Hong-Gyun; Lee, Joon-Hyuk; Flausino, Lucas E; Quintana, Francisco J (Science translational medicine, 2023)
Astrocytes are abundant glial cells in the central nervous system (CNS) that play active roles in health and disease. Recent technologies have uncovered the functional heterogeneity of astrocytes and their extensive interactions with other cell types in the CNS. In this Review, we highlight the intricate interactions between astrocytes, other CNS-resident cells, and CNS-infiltrating cells as well as their potential therapeutic value in the context of inflammation and neurodegeneration.